ChemInform Abstract: Organocatalyzed Formal [2 + 2] Cycloaddition of Ketimines with Allenoates: Facile Access to Azetidines with a Chiral Tetrasubstituted Carbon Stereogenic Center. Issue 1 (7th January 2014) - Takizawa, Shinobu; Arteaga, Fernando Arteaga; Yoshida, Yasushi; Suzuki, Michitaka; Sasai, Hiroaki
Abstract The title reaction is highly E‐selective and provides azetidines in good yields with high enantioselectivities.